Segurança do paciente: conhecimento de alunos de um curso técnico em enfermagem - Silva, Ana Paula Falcoski Martinelli (Universidade Federal de São Carlos, 2022)
The care complexity and the performance of several procedures make the nursing professional's routine prone to errors. One strategy is to include the topic of patient safety in teaching, as risk recognition and prevention of adverse events are fundamental in the training of future professionals. Given the relevance of the topic and considering that nursing professionals at a technical level predominate in number in institutions, the importance of taking actions related to patient safety content for the technical course student is highlighted. There is a gap in the content related to teaching on the subject and the training of this professional has weaknesses in this aspect. COVID-19 has disorganized the health system and the complications resulting from the disease have overloaded care in health institutions. The job offer increased, mainly for the nursing technicians category. The research’s objective was to evaluate the knowledge of students of a technical course in nursing about patient safety. It was a methodological development study with a quantitative approach in which it was proposed the construction and validation of a structured instrument to assess students' knowledge about patient safety and a descriptive research where the instrument was applied. The present study took place in a state technical school in the city of São Carlos and was developed in 2 phases: phase 1, consisting of the construction and validation of the instrument by expert judges; and phase 2 consists of the application of the instrument to the students. The instrument developed followed as a model the Student Assessment Instrument regarding teaching about quality and safety in nursing QSEN SES BR with the domains: patient-centered care, safety, teamwork and collaboration and informatics. The CVI was 0.89 and Cronbach's Alpha was 0.751. Subsequently, the instrument called Student Assessment Questionnaire on Patient Safety (QAESP), which has 15 questions on patient safety, was applied to 51 students (46% response rate), of which 94.1% were female, average age aged 31.5 years and 35.3% with experience in providing care to patients, 56.5% being caregivers for the elderly. Of the total number of students, 90.2% agreed that requesting help from another health professional, and recognizing the importance of intra and interprofessional collaboration, is essential for teamwork; 86.3% agreed that they always inform the teacher about the presence of conditions that favor the occurrence of avoidable care incidents in the internship field; 86.3% agreed that health technologies improve the quality of care and contribute to increasing the safety of patient care, and 52.9% agreed that information systems, to report the occurrence of preventable care incidents, make a difference in reducing future mistakes. The topic is not included in the technological bases of the course. Despite the importance of the topic, the results point to the improvement of actions that can lead to vulnerable care. The study showed that the QAESP is a valid tool for evaluating the teaching of patient safety by nursing technicians.
Patienty safety: knowledge of students of a technical nursing course
Keywords: Segurança do paciente; Enfermagem; Ensino; Técnico de enfermagem; Patient safety; Nursing; Teaching; Nursing technicians; CIENCIAS DA SAUDE::ENFERMAGEM